2019
DOI: 10.3390/polym11101546
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanical Properties of Ionic Di-block Copolymers via a Molecular Dynamics Approach

Abstract: Polymerized ionic copolymers have recently evolved as a new class of materials to overcome the limited range of mechanical properties of ionic homopolymers. In this paper, we investigate the structural and mechanical properties of charged ionic homopolymers and di-block copolymers, while using coarse-grained molecular dynamics simulation. Tensile and compressive deformation are applied to the homopolymers and copolymers in the glassy state. The effect of charge ratio and loading direction on the stress-strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…When the pressure in different coordinate directions is adjusted separately, the cubic simulation box changes its shape due to the anisotropic nature of the system. The length of the lamellar phase increases perpendicularly to the interface accompanied by the shrinkage along the other directions, as mentioned in our previous work [19] and similar to the work by Lee and co-workers. [20] The elongated direction has been observed to be in the direction perpendicular to the microphase interface.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…When the pressure in different coordinate directions is adjusted separately, the cubic simulation box changes its shape due to the anisotropic nature of the system. The length of the lamellar phase increases perpendicularly to the interface accompanied by the shrinkage along the other directions, as mentioned in our previous work [19] and similar to the work by Lee and co-workers. [20] The elongated direction has been observed to be in the direction perpendicular to the microphase interface.…”
Section: Introductionsupporting
confidence: 89%
“…As evidenced in our previous studies, the presence of ions will increase the Tnormalg, which has been shown to increase with the charge ratio up to 50%. [ 19,24 ] On the other hand, the interaction at the interface is weaker than that in the interior of the microphase. The larger interface area may also lower the glass transition temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is used in biomedicine [ 3 , 4 ], microfluidics [ 5 , 6 , 7 ], MEMS [ 8 ], triboelectricity [ 9 ] and piezoelectrics [ 10 ]. Motivation to explore the structure and dynamics of ionic PDMS [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] or other melts [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], is very high since ionic interactions inherit polymers with a functionality that leads to a high performance and applications as gas-separating membranes [ 15 ], water purification membranes [ 13 , 14 , 16 ], energy storage devices [ 39 , 40 ] as well as in sensing [ 22 , 23 ], actuation [ 21 ], fuel cells [ 41 ], and others [ 18 , 19 , 24 , 42 ].…”
Section: Introductionmentioning
confidence: 99%